Strategi Penciptaan Pelayanan Kesehatan Dasar untuk Kemudahan Akses Penduduk Desa Miskin - Sunyoto Usman; Derajad S. Widhyharto; Amelia Maika (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Improving health care service access for the poor is a complex and challenging effort. Various health care facilities are often located in hardly accessible spots for the poor. This research seeks to develop policy options that can be used to create primary health care services became more accessible to the poor. A mobile facility-based health care service system or a service system which allows accessible health facility for the society, especially the poor, needs to be developed. This system needs regulation, institutional, human resources and financial support, and also good coordination among institutions which have related functions and duty on primary health care services.